Remain True to the Culture? Authenticity, Identity, and Association of United Ukrainian Canadians Sponsored Dance Seminars, 1971 to 1991 - Staniec, Jillian (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
AbstractA series of dance seminars was held in Ukraine and Saskatchewan from 1971 to 1991, hosted by a left-wing political and cultural organization, the Association for United Ukrainian Canadians. These seminars heavily influenced the development of Ukrainian dance in Saskatchewan and Canada by introducing new dance techniques, choreography, and costuming from Soviet Ukraine. They were also very controversial, challenging the definition of Ukrainian Canadian identity in Canada during the Soviet era.